Biochemical Changes in Disease. - Cardoso, Inês Lopes (Cambridge Scholars Publishing, 2022)
This book explores and identifies the main biochemical changes that occur in several diseases, including those of pancreatic, cardiovascular, musculoskeletal, psychiatric, nutritional, and infectious origin. It also considers the recognition of possible biochemical markers of each disease, highlighting how they can be used in diagnosis.